Houses, pots and food - Mlekuž, Dimitrij (Documenta Praehistorica, 2012)
In this paper, we attempt a multiscalar analysis of the Maharski prekop archaeological site, connecting the landscape context, temporal dynamics, and spatial organisation with the composition of the artefact assemblage, the shapes, sizes and technological composition of the pottery, and traces of activities in the form of food residues on pottery. The pottery assemblage from Maharski prekop is characterised by a wide variation in vessels. This canbe explained by the non-specialised use of vessels, where they were deliberately designed to be able to perform a series of different functions, which is supported by the technological analysis of fabrics and the wide rangeof identified foodstuffs, interesting contexts with an abundance of anthropomorphic figurines are presented and discussed.
Keywords: arheološka najdišča; bakrena doba; Ljubljana; Ljubljana Marshes; Ljubljansko barje; lončevina; posodje